Perencanaan Pembangkit Listrik Tenaga Surya (PLTS) Sistem Hybrid Pada Jaringan Kelistrikan Di Rumah Sakit Umum Yarsi Pontianak - Sanjaya, Rhendy Eka; Gianto, Rudi; Junaidi, Junaidi (Journal of Comprehensive Science, 2024)
Electrical energy is very important in everyday life to support the activities of various sectors. Fossil fuels as an energy source are a top priority, therefore renewable energy is an alternative to replace the limitations of fossil fuels which is the main priority in efforts to generate electrical energy in Indonesia. The high intensity of sunlight in Indonesia, especially in Pontianak City, is very suitable for building a Solar Power Plant (PLTS). The aim of this research is to find out how much potential PLTS has using applications PVsyst 7.3by utilizing the roof of the hospital building. This research uses three methods for economic analysis and analyzing the feasibility of PLTS. The method used isNet Present Value (NPV), Profitability Index (PI), and Discounted Payback Period (DPP). The results of research carried out using Software PVsyst 7.3 It was found that the PLTS system was installed on the roof of YARSI Pontianak General Hospital with a slope angle of 4O namely 115 kWp with the type of solar panel used being the Jinko Solar Tiger Neo N-type 72HL4-BDV 580Wp 198 units, 3 inverters of the SUN2000-30/36/40KTL-M3 type with a capacity of 40 kW, and batteries with type Sunlight RES OPzS with a capacity of 3060 Ah. Based on the results of calculations that have been carried out, the initial investment required is IDR. 1,578,472,422. Analysis of the economic feasibility of PLTS using 3 methods has been carried out to obtain an NPV value of Rp. 797.610.941,86, PI value of 1.505, and DPP value of 14 years. The three methods used in this research show that PLTS is feasible.